Inconsistent Condom Use among Public Primary Care Patients with Tuberculosis in South Africa - Gladys Matseke; Karl Peltzer; Julia Louw; Pamela Naidoo; Gugu Mchunu; Bomkazi Tutshana (The Scientific World Journal)
The high rate of HIV infections among tuberculosis (TB) patients in South Africa calls for urgent HIV reduction interventions in this subpopulation. While correct and consistent condom use is one of the effective means of HIV prevention among sexually active people, there is insufficient research on condom use among TB patients in South Africa. The aim of this paper was to determine the prevalence of inconsistent condom use among public primary care TB patients and its associated factors using a sample of 4900 TB patients from a cross-sectional survey in three health districts in South Africa. Results indicated that when asked about their consistency of condom use in the past 3 months, 63.5% of the participants reported that they did not always use condoms. In the multivariable analysis, being married (OR=1.66; 95% CI 1.25–2.20) or cohabitating or separated, divorced, or widowed (OR=3.67; 1.85–7.29), lower educational level (OR=0.66; 0.46–0.94), greater poverty (OR=1.60; 1.25–2.20), not having HIV status disclosed (OR=0.34; 0.25–0.48), sexual partner on antiretroviral treatment (OR=0.38; 0.23–0.60), and partner alcohol use before sex (OR=1.56; 1.30–1.90) were significantly associated with inconsistent condom use in the past 3 months. The low proportion of consistent condom use among TB patients needs to be improved.